2006
DOI: 10.1063/1.2354991
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Spin-transfer Torque in SFNFS Junctions

Abstract: Abstract. We report theoretical results for the nonequilibrium spin current and spin-transfer torque in voltage-biased SFNFS Josephson structures. The subharmonic gap structures and high voltage asymptotic behaviors of the dc and ac components of the spin current are analyzed and related to the spin-dependent inelastic scattering of quasiparticles at both F layers. Spin-polarized current passing through a ferromagnet can transfer spin angular momentum to the ferromagnet and exert a torque on the magnetic momen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Due to the importance of Josephson junctions in numerous applications the Josephson effect has been subject of intense theoretical study. The current-phase relation as well as the oscillation of the electron transport in a voltage biased point contact known as the ac-Josephson effect has been theoretically investigated for different situations 9,10,11 including unconventional superconductivity 12 , spin active magnetic barriers 13,14,15 and the effect of pair breaking due to disorder 16 . It has been shown that within the quasiclassical theory interfaces can be described by effective boundary conditions 17 that can be included by mainly two different approaches: the scattering-matrix approach and the transfer-matrix approach 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of Josephson junctions in numerous applications the Josephson effect has been subject of intense theoretical study. The current-phase relation as well as the oscillation of the electron transport in a voltage biased point contact known as the ac-Josephson effect has been theoretically investigated for different situations 9,10,11 including unconventional superconductivity 12 , spin active magnetic barriers 13,14,15 and the effect of pair breaking due to disorder 16 . It has been shown that within the quasiclassical theory interfaces can be described by effective boundary conditions 17 that can be included by mainly two different approaches: the scattering-matrix approach and the transfer-matrix approach 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Equilibrium density of states was also studied 4,5 . On the other hand, to the best of our knowledge, the nonequilibrium transport in SFS mesoscopic junctions has not been studied yet neither from theoretical nor from experimental point of view except for theoretical investigations of magnetic quantum point contacts 6,7,8,9 . We address our theoretical paper to the part of this problem and study the phase-coherent transport in diffusive voltage-biased SFS plane junctions.…”
mentioning
confidence: 99%